Ethnobotany of the genus Elatostema J.R. Forster & G. Forster - Upadhyay, Ashutosh Kumar; Gogoi, Rajib; Mitra, Prashanta Kumar (Ethnobotany Research and Applications, 2021)
Background: Wild edible plants (WEP’s) are used in various traditional systems all over the globe. WEP’s are used as food, medicine, ornamental, forage and material purposes. Elatostema is one such genus that is used by many indigenous communities in Africa, Asia and Oceania. The objectives of this study are to provide ethnobotanical information about the non-stinging nettle genus Elatostema, to identify indigenous communities that use these species and to examine leaf area variation in species used by ethnic communities. Methods: The data sets were collected from various online sources such as Research gate, Google Scholar and Academia.edu; print sources such as published articles in ethnobotanical journals and herbarium sources from various herbaria. The datasets were then segregated into four types (Consumption, medicinal, Forage and other) based on the recorded usage by indigenous communities all over the globe. We analyzed leaf variation with type of usage using density plots, Shapiro-Wilks test, Kruskal-Wallis test and Principal Component Analysis (PCA). The Use-Value (UV) of all species was also calculated using the number of recorded usage and their citations within the genus. Results: This study documented 40 Elatostema species with recorded ethnobotanical usage. We record 30 indigenous communities that use species of Elatostema in their daily lives. After performing all the analysis (density plots, Shapiro-Wilks test, Kruskal-Wallis test and Principal Component Analysis) we found out that there is no significant variation in leaf area with the type of use. Elatostema platyphyllum Wedd. and Elatostema sessile J.R. Forster & G. Forster were found to have low values (UV=0.18 and UV=0.23) because of high recorded usage and citations. Conclusion: This study illustrates diversity of Elatostema species used as food, medicine, forage and ornamental or material purposes by various indigenous communities in the world. The study disproves our hypothesis that the usage of an Elatostema species for a specific purpose (food, medicine, fodder, others) is related to leaf size, i.e., bigger the size of the leaves, more the chances of it to be used as food or forage. Results from our analyses shows that there is no variation in leaf area with the type of use. The documented ethnobotanical records of Elatostema species along with our personal observations in the field provided in this study would help in elucidating the importance of this genus as one of the main leafy wild edible plant for human consumption and will further promote applied research in this group. Key words: Elatostema, Urticaceae, ethnobotany, Indigenous communities, Analysis